2020
DOI: 10.22237/jotm/1577854980
|View full text |Cite
|
Sign up to set email alerts
|

Drug Testing in the U.S. Trucking Industry: Hair vs. Urine Samples and the Implications for Policy and the Industry

Abstract: Virtually everything we own was transported by truck at some point. Around 3.5 million truck drivers haul almost 71% of U.S. freight. To ensure the safety of our roadways, the U.S. government requires all drivers to pass urinalysis drug screens. However, urinalysis drug screens are easily thwarted and some trucking companies use hair drug screens, a more stringent test. This research examines trucking industry data and finds about 300,000 truck drivers would be removed from their positions if forced to pass a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Voss and Cangelosi [25] found that 276,500 current drivers would be unable to legally operate a commercial motor vehicle if hair testing was required. Mitra [3] found that poor performance in the controlled substances BASIC increases the likelihood of motor carrier crashes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Voss and Cangelosi [25] found that 276,500 current drivers would be unable to legally operate a commercial motor vehicle if hair testing was required. Mitra [3] found that poor performance in the controlled substances BASIC increases the likelihood of motor carrier crashes.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from Voss and Cangelosi [25], Gordon et al [7], and Henriksson [26], the literature on supply chains is largely silent on drug testing in the trucking industry.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 3 more Smart Citations